Subsurface Clay Soil Application Improved Aggregate Stability, Nitrogen Availability, and Organic Carbon Preservation in Degraded Ultisols with Cover Crop Mixtures. Issue 3 (1st May 2019) - Ye, Rongzhong; Parajuli, Binaya; Sigua, Gilbert
Abstract : Core Ideas: Subsurface clay soil amendment improved soil aggregation and its stability. Microbial activities were suppressed by clay soil applications. Clay soil amendment enhanced labile organic C pools. Additions of clay soil promoted ammonium fixation and reduced nitrate leaching. Coastal Plain soils of the southeastern United States are highly degraded, with low soil organic carbon (C), meager soil fertility, and poor soil structure. We tested the effectiveness of clay soil amendment to promote the formation of soil aggregates, improve organic C stability, and enhance nutrient availability in field. Subsurface clay soils (B horizon, 25% clay) were applied (∼25 T ha –1 ) to the top of the soil surface, followed by the planting of winter cover crop mixtures. Crop growth and nutrient uptake and relevant soil biogeochemical properties were analyzed at the end of the winter season. Additions of subsurface clay soils prompted the formation of water‐stable macroaggregates (250–2000 mm) from 32 to 54% and increased mean weight diameter of the aggregates from 390 to 592 mm. Additions of subsurface clay soils increased clay content from 1.5 to 3.8% but did not change soil texture, pH, water holding capacity, and bulk density. The stock of dissolved organic nitrogen was not affected by the amendment, whereas nitrate leaching from field was reduced by 61% because of clay soil application. Clay soil additions inhibited the activities of C‐cycling (N‐acetyl‐β‐glucosaminidase, β‐d ‐cellubiosidase, β‐glucosidase, and β‐xylosidase) and N‐cycling (leucine aminopeptidase) enzymes but did not modify soil microbial community level substrate utilization patterns, resulting in a 63% reduction in C turnover rate and 19% increases in concentrations of labile organic C. Our results indicated that subsurface clay soil amendment can improve soil structure, nutrient availability, and the stability of labile C in the field, at least in the short term, and may be a promising management alternative to enhance the productivity and sustainability of the degraded Coastal plain soils.